Refusal Politeness Strategies of The Main Characters in ‘It Starts with Us’ A Novel by Colleen Hoover - Diah Supatmiwati; Chaerul Ihsanul Mubin; Ketut Putri Nila Sudewi; Wiya Suktiningsih (Humanitatis : Journal of Language and Literature, 2023)
This study aims to analyze the types of refusal politeness strategies used by or towards the main characters in ‘It Starts with Us’ a novel that was published in late 2022 by Colleen Hoover, which was a sequel for the previous book by the same author titled ‘It Ends with Us’. To reveal the refusal politeness strategies, the researcher decided to use the politeness theory by Brown and Levinson (1987), and the data were then analyzed by using qualitative descriptive. The result of this research were the 9 data , which contained the refusal politeness strategies. All nine of the data mentioned in this study are direct refusal,with predominantly positive politeness strategies, with six of nine data being positive politeness strategies, but the variety employed varied. The remaining three data were negative politeness strategies, which is composed of two indirect strategies and an apology.